2011
DOI: 10.1089/ten.tec.2011.0255
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Clinical-Grade Expansion of Mesenchymal Stem Cells from Human Sources: A Microcarrier-Based Culture System Under Xeno-Free Conditions

Abstract: The immunomodulatory properties of mesenchymal stem cells (MSCs) make them attractive therapeutic agents for a wide range of diseases. However, the highly demanding cell doses used in MSC clinical trials (up to millions of cells/kg patient) currently require labor intensive methods and incur high reagent costs. Moreover, the use of xenogenic (xeno) serum-containing media represents a risk of contamination and raises safety concerns. Bioreactor systems in combination with novel xeno-free medium formulations rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
195
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(222 citation statements)
references
References 35 publications
(48 reference statements)
18
195
1
4
Order By: Relevance
“…High yield MSC expansion on similar microbead carriers has been previously demonstrated for both rat 23,24 and human cells. 25,26 Unlike these prior reports, we expanded these cultures by adding media and microbead carriers, while retaining the nonadherent cellular fractions. The rationale behind this approach is to allow for the retention of Green fluorescent cells were isolated by plating from bioreactor MSCs injected rat arterial blood, but not from the monolayer MSCs experiments (inset).…”
Section: Discussionmentioning
confidence: 99%
“…High yield MSC expansion on similar microbead carriers has been previously demonstrated for both rat 23,24 and human cells. 25,26 Unlike these prior reports, we expanded these cultures by adding media and microbead carriers, while retaining the nonadherent cellular fractions. The rationale behind this approach is to allow for the retention of Green fluorescent cells were isolated by plating from bioreactor MSCs injected rat arterial blood, but not from the monolayer MSCs experiments (inset).…”
Section: Discussionmentioning
confidence: 99%
“…Cultispher-S (Eibes et al 2010), Cultispher-G (Sun et al 2010) and SoloHill Plastic P102-L (Dos Santos et al 2011). However in all the aforementioned studies, the largest volume used was no more than 200 mL and it is unclear as to whether samples of microcarrier suspension greater than 2 mL were harvested.…”
Section: Introductionmentioning
confidence: 99%
“…These microcarriers were selected based on their suitability for the culture of hMSCs relative to a number of other microcarriers as identified in previous unpublished studies conducted by the authors (data not shown) as well as other groups (Dos Santos et al 2011), in addition to their amenability for good manufacturing practise (GMP) bioprocesses, given their xeno-free composition. Whilst it would be possible to control the pH and dO 2 levels in the bioreactors, it was decided that this investigation would be used to monitor and identify the change in pH and dO 2 over the course of the culture as there is little work in the literature which identifies the optimal pH and dO 2 levels for microcarrier hMSC culture.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, serum free culture is a direction in the future standardized production of biological products with bioreactors [51,52]. It is necessary to investigate the metabolic characteristics of SCs in large scale expansion of cells, design the key components in the serum free medium and optimize the physical and chemical properties of the medium, which may develop individualized culture medium [53]. This, together with appropriate fed-batch or perfusion strategies, may assure the key nutrients at appropriate levels, which reduces the production of toxins and is suitable for large-scale cell expansion [10,54].…”
Section: Nutrient Supply and Metabolismmentioning
confidence: 99%